2019
DOI: 10.1039/c9cc02021g
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular synthon approach to design amorphous solid dispersions with exceptional physical stability

Abstract: A supramolecular synthon approach was exploited to design amorphous solid dispersions (ASDs) of drugs containing an amino aromatic nitrogen moiety and a polyacrylic acid polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 21 publications
6
53
0
Order By: Relevance
“…S9, ESI † ), absorption at 1706 cm −1 is attributed to the carbonyl stretching of carboxylic acid dimer in the polymer matrix. 31 This signal is shifted to 1725 cm −1 in the grafted azomaterials ( Fig. 4 and Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…S9, ESI † ), absorption at 1706 cm −1 is attributed to the carbonyl stretching of carboxylic acid dimer in the polymer matrix. 31 This signal is shifted to 1725 cm −1 in the grafted azomaterials ( Fig. 4 and Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The double hydrogen bond occurring between a carboxylic acid group and a 2-aminopyridine type moiety is recognized as a robust supramolecular heterosynthon in crystal engineering and proved as a useful tool to produce stable amorphous solid dispersions. 30,31 In this work, we designed new supramolecular azopolymers by grafting 2-aminopyrimidine functionalized azochromophores onto polyacrylic acid (PAA) and investigated the efficiency of SRG formation. 32 A comparative study of SRG inscription performances with a single H bonded system revealed a very strong influence of the supramolecular synthon on the efficiency of mass migration.…”
Section: Introductionmentioning
confidence: 99%
“…The high drug loading achieved exceeds the levels reported previously. 20 22 Despite elevated stability, the amorphous salt shows fast dissolution in biorelevant media. Furthermore, the amorphous CFZ–PAA salt shows improved tabletability and powder flow relative to crystalline CFZ.…”
Section: Discussionmentioning
confidence: 99%
“…The basic polymer Eudragit E PO has been used to stabilize acidic drugs naproxen 20 and indomethacin; 21 the acidic polymer poly(acrylic acid) (PAA, Carbomer) has been used to stabilize 2-aminopyridine-containing basic drugs. 22 The recent work on polymer nanocoating takes advantage of the local formation of drug–polymer salts. For example, the basic polymer chitosan is deposited on the surface of the acidic drug indomethacin, 8 and the acidic polymer alginic acid is deposited on the surface of the basic drug clofazimine.…”
Section: Introductionmentioning
confidence: 99%
“…The solid-phase forms of active pharmaceutical ingredients (APIs), including polymorphous materials (Ito et al, 2018), amorphous materials (Duggirala et al, 2019), hydrates (Gaztañ aga et al, 2018), solvates (Minkov et al, 2014), salts (Zhang et al, 2016) and co-crystals (Dai et al, 2018), are related to their physicochemical properties, such as stability (Sugimoto et al, 2013) and solubility (Jensen et al, 2017), and the form further influences its bioavailability and clinical efficacy (Song et al, 2019). Thus, determining the solid form of an API receives great attention.…”
Section: Introductionmentioning
confidence: 99%